The Impact of Genetic Research and Discoveries During the Past Century on Behaviour (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article examines the relationship between genetics and behaviour over the past century as part of the series "WHAT THEY DID TO YOU - 100 YEARS AGO." The series delves into various aspects of genetics and its wide-reaching effects on behaviour, environment, and human development. The exploration begins with a thorough understanding of the fundamental principles of genetics, discussing how genes serve as the blueprints of life encoded in DNA, influencing every aspect of our being from physical traits to complex behaviours. By understanding genetic inheritance, mutations, and diversity, we can better appreciate the intricate interplay between our genes and our lives. Future articles will expand to explore how genetic predispositions affect behavioural tendencies and personality traits; the dynamic interaction between our genetic makeup and environmental factors, including epigenetic changes; how our five senses shape our thoughts, decisions, and overall lifestyle; and the genetic and environmental influences on fetal development from conception to birth. This series aims to provide a comprehensive understanding of how genetics has shaped our lives over the past century and how we can use this knowledge to influence future outcomes. By unravelling the complex web of genetic and environmental interactions, this research hopes to offer insights into the profound impact of our genetic legacy and the potential for shaping a better future.